2019
DOI: 10.1167/iovs.19-27055
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Retinal and Choriocapillaris Perfusion in Different Stages of Macular Telangiectasia Type 2

Abstract: PURPOSE. To quantify the retinal and choriocapillaris perfusion in different disease stages of macular telangiectasia type 2 (MacTel) using optical coherence tomography-angiography (OCT-A). METHODS. We examined 76 eyes of 76 patients and 24 eyes of 24 age-related controls. Participants underwent multimodal imaging, including OCT and OCT-A. Patients' eyes were divided into three groups considering predefined criteria from funduscopy, OCT, and fluorescein angiography, thus reflecting the disease severity (''earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Several previous studies have described various morphological changes that would fit into the category of hyperreflectivity on OCT. [6][7][8][9] Possible anatomical correlates of hyperreflectivity include altered retinal capillaries, retinal-choroidal anastomoses, migrating pigment cells, and neurodegenerative processes. 6,[9][10][11] Optical coherence tomography angiography has been helpful as an imaging tool for illustrating disease-associated changes of the retinal and choroidal microvasculature, 12,13 permitting a detailed visualization of neovascularizations secondary to MacTel. 14 Unlike OCT, however, OCT-A is currently not widely available in clinical practice.…”
mentioning
confidence: 99%
“…Several previous studies have described various morphological changes that would fit into the category of hyperreflectivity on OCT. [6][7][8][9] Possible anatomical correlates of hyperreflectivity include altered retinal capillaries, retinal-choroidal anastomoses, migrating pigment cells, and neurodegenerative processes. 6,[9][10][11] Optical coherence tomography angiography has been helpful as an imaging tool for illustrating disease-associated changes of the retinal and choroidal microvasculature, 12,13 permitting a detailed visualization of neovascularizations secondary to MacTel. 14 Unlike OCT, however, OCT-A is currently not widely available in clinical practice.…”
mentioning
confidence: 99%
“…The flow voids of our pretreatment and posttreatment cases were greater than previously reported normal choriocapillaris flow voids: 11.5% to 17.7%. 5,11 However, a comparison cannot be made because these normative values were derived from 3 Â 3-mm scans and we used 8 Â 8-mm scans. A described normative value and longer follow-up will allow comparison of normal, pretherapy and posttherapy eyes to assess whether residual choriocapillaris dysfunction persists despite normalization of funduscopic examination, as may be suggested by the difference in posttherapy choriocapillaris flow voids in the right (30.7%) and left eye (33.9%) of case 1.…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, CC VD pictures were analysed with specifically designed software. First, every pixel was codified into a number following this scale: dark blue (1), blue (2), light blue (3), cyan (4), green (5), yellow (6), orange (7), red (8) and dark red (9). Then, pictures were divided into a grid of 900 squares (30 rows and 30 columns) with the same size.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that CC plays a major role in different retinal pathologies such as age-related macular degeneration, 4,5 systemic hypertension,6 myopic maculopathy, 7 macular telangiectasia type 2, 8 retinal dystrophies, 9 or inflammatory choriocapillaropathies. 10 Choroidal vascularization remains difficult to measure due to light scattering when passing through the overlaying tissues and the retinal pigmentary epithelium (RPE).…”
Section: Introductionmentioning
confidence: 99%